Castleman disease and paraneoplastic pemphigus in a pregnant woman: A case report. Issue 13 (2nd April 2021) - Cui, Beibei; Lin, Hui
Abstract: Rationale: Orogenital ulcers can be observed in various conditions, such as Behcet disease, infection and also paraneoplastic pemphigus (PNP). Castleman disease (CD), which is a rare cause of paraneoplastic pemphigus represents a heterogenous lymphoproliferative disorder of unknown etiology. Paraneoplastic pemphigus associated with CD in pregnancy is rare and has not been reported yet. Patient concerns: We report a rare case of CD in a 26-year-old pregnant woman with orogenital ulcers. The patient suffered from mucosal erosions and uveitis at 23 weeks of gestation. A retroperitoneal mass (9.7×7.3×11.8 cm) was identified by CT scan. Diagnoses: According to histological and immunohistological findings, a diagnosis of unicentric CD, hyaline vascular type, and PNP was formulated. Intervention: High dose methylpredisonlone was given for the therapy. Pancreatic uncinatectomy, portal vein and superior mesenteric vein repair, pancreaticojejunostomy, and caesarean section were performed on the patient to remove the tumor and the fetus. Outcomes: The fetus did not survive after surgery. The patient did not achieve remission and she died from epidermolysis and sepsis several months later. Lessons: PNP associated with CD is a rare lymphoproliferative disorder and needs to be differentiated from other orogenital diseases by histological features. Ethics and dissemination: Written informed consent was obtained from the patient for publication of this case report and accompanying images. Ethical approval of this study was granted by the Ethics Committee of West China Hospital of Sichuan University. (Ethics Reference No: 2021143).